(untitled) (Fiep Bulletin - online, 2013)
The pressure ulcers (PU) are skin lesions of the soft parts, superficial or deep part, of etiology ischemic, secondary to an increase of external pressure. His predominance still is elevated in patients hospitalized and can occur in all of the age groups, but in private with elderly persons that live in a range of conditions. The identification of UP and his risks are important for its prevention in the elderly population. The objective of that study is, then, identify the factors of risk involved in the sprouting of UP in elderly patients hospitalized in Intensive Care Unit (ICU) in a private hospital and a public of the town of Christmas/RN. Treats-itself of a descriptive study with longitudinal delineation and quantitative approach with population 41 elderly boarding in ICU. The facts were collected after approval by the Committee of Ethics of the HUOL/UFRN (RESOLUTION 196/96) being carried out on the basis of form structured, obtaining of facts of the manuals and physical exam of the skin of the patients. Of the 41 patients researched, 51.2% were of the female sex and 51.2% developed UP. Of those who develop PU, 76.2% presented association of more of 3 predisposing conditions, 76.2% presented the association of more of 5 inherent factors and 76.2% association between more of four extrinsic factors. As regards the location of the wounds, 57.1% developed in the region sacral and 28.6% in the calcâneo. We observe that exists an association between the predisposing conditions, extrinsic and inherent factors in the occurrence of UP in the sick elderly, what is done Important seek information of the influence of the multiplicity of factors and conditions that increase the risk of occurrence of UP, in the perspective of contribute with the prevention and diminution of its complications.